Prediction of high-resolution reservoir facies and permeability, an integrated approach in the Irwin River Coal Measures Formation, Perth Basin, Western Australia - Elkhateeb, Abdelrahman; Rezaee, Reza; Kadkhodaie, Ali (ELSEVIER, 2019)
Traditionally, prediction of facies and permeability for a reservoir rock was one of many challenges in the industry that necessitates advanced and sophisticated evaluation for effective reservoir description. Three wells have been studied in the Perth Basin in Western Australia across the shaly sand of the Irwin River Coal Measures Formation, which contain a comprehensive suite of advanced and conventional logs. Due to the reservoir heterogeneity and the clay distribution, it is very challenging to resolve the effective pore volume, the reservoir facies and how the high permeability zones are distributed within the formation. In this paper, a new technique has been successfully tested on the Shaly Sand by integrating the nuclear magnetic resonance (NMR) and the conventional density log. The method allows the establishment of high-resolution facies classification for the reservoir using an Equivalent Flow Zone Indicator Index (EFZI). The studied core facies have been integrated with the EFZI into a new workflow to distribute facies on a larger scale in the uncored wells. Four hydraulic flow units (HFU) have been defined from one cored well using Flow Zone Indicator approach, with each has a unique FZI value and different permeability model based on core measurements. The EFZI-based high-resolution facies have been validated at several formation depths using the core thin sections to ensure the best calibration will be obtained for facies log, hence the permeability log-to-core match. The methodology will help running an advanced petrophysical analysis for the zone of interest and will reduce the parameters uncertainty. Application of this methodology in the uncored wells has shown very encouraging results, which is believed it can be used in the absence of any core data to resolve the rock typing from the well logs.